Focal depth measurements of the vaginal wall: a new method to noninvasively quantify vaginal wall thickness in the diagnosis and treatment of vaginal atrophy. Issue 8 (August 2016) - Weber, Maaike A.; Diedrich, Chantal M.; Ince, Can; Roovers, Jan-Paul
Abstract: Objective: The aim of the study was to evaluate if vaginal focal depth measurement could be a noninvasive method to quantify vaginal wall thickness. Methods: Postmenopausal women undergoing topical estrogen therapy because of vaginal atrophy (VA) were recruited. VA was diagnosed based on the presence of symptoms and vaginal pH at least 5.5. The control group consisted of women above 40 years without VA. Focal depth measurements were performed before and after treatment using the Cytocam-Incident Dark Field device assessing the distance between the subepithelial microcirculation and the epithelial surface. Measurements were performed before and after treatment in the intervention group and at two different time points in the control group. Vaginal pH was measured. Symptoms were evaluated using the most bothersome symptom approach. Results: Eight women with VA and nine controls were included. Pretreatment median focal depth was not significantly different between both groups. Pretreatment focal depth more than doubled after a median of 7 weeks of topical estrogen treatment (80 μm [interquartile range 80-120 μm] vs 220 μm [148-248 μm], P   =  0.02), whereas the measurements in the control group did not change. Pretreatment vaginal pH differed between both groups (5.5 vs 5.1, respectively, P  < 0.01). Vaginal pH did not change after treatment. Conclusions: Using in vivo microscopy we introduced a new noninvasive measure of vaginal wall thickness. A significant increase in vaginal focal depth was observed in participants with VA treated with topical estrogens. This innovative measurement of vaginal wall thickness could become the preferred objective measure to evaluate treatment effect. Moreover, it has great potential for other applications in the field of urogynecology.